Співробітництво Академічного центру компетенції SAP СПбДПУ та вищих навчальних закладів країн СНД у межах програми "Університетський Альянс SAP" - Arseniev, D. G.; Ambrajei, A. N.; Golovin, N. M.; Taratoukhine, V. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2011)
The main tasks of SAP Academic Competence Centre in SPBSPU — the main university focal point of the "SAP University Alliances Program" is CIS region, are considered. The article describes the main activities of the Centre such as building cooperation with universities in Russia, Ukraine and Belarus, establishing of training courses, organizing the teacher training and supporting of the professional certification system.